Glass article and display device including same
By adjusting the composition ratio and manufacturing process of glass products and improving their impact resistance characteristics, the problem of easy damage to existing thin glass products under external impact is solved, and the effect of providing excellent flexibility and strength in a foldable display device is achieved.
Patent Information
- Application Number
- CN202411036752.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-31
- Filing Date
- 2024-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
The existing thin glass products are unbearable under external impact and are prone to damage due to bending stress in foldable display devices.
By adjusting the composition ratio and manufacturing process of glass products, it can improve its fracture energy index, elastic performance index and free volume index, so that it has excellent impact resistance. Specific measures include controlling the thickness of the glass product in the range of 20 μm to 150 μm, optimizing its physical properties index, such as the first elastic performance index, the second elastic performance index, the fracture energy index, the first free volume index, etc.
The excellent impact resistance characteristics of the glass products in the thickness range of 20 μm to 150 μm are achieved, which can effectively resist external impacts and provide excellent flexibility and strength in the foldable display device.
Smart Images

Figure CN119430650A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the priority of Korean Patent Application No. 10-2023-0100092 filed in the Korean Intellectual Property Office on July 31, 2023, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0003] Embodiments of the present disclosure relate to a glass article and a display device including the same. Background Art
[0004] Glass products are widely used in electronic devices or building materials including display devices. For example, glass products can be incorporated into a substrate of a flat panel display device (such as a liquid crystal display (LCD) device, an organic light emitting display (OLED) device, or an electrophoretic display device) or a cover window protecting it.
[0005] As portable electronic devices such as smartphones and tablet personal computers (PCs) become popular, glass products used therein are frequently exposed to external impacts. Therefore, there is a need for a thin portable glass product that can withstand external impacts.
[0006] In recent years, a foldable display device has been developed for user convenience. Glass products incorporated into the foldable display device should be thin to alleviate bending stress caused when being folded, and should be strong to withstand external impact. Therefore, attempts have been made to improve the strength of thin glass products by changing the composition ratio of the glass products and the manufacturing process conditions. Summary of the invention
[0007] Embodiments of the present disclosure provide a glass article and a display device including the same, which are defined such that an index of a specific physical property satisfies a predetermined value to have an increased anti-impact characteristic.
[0008] The glass article according to one embodiment may have a fracture energy index, an elastic energy index, and a free volume index higher than or equal to a predetermined value, and thus has excellent impact resistance. Due to the foldable characteristics of the glass article, a display device including the glass article may have excellent flexibility and strength.
[0009] According to an embodiment of the present disclosure, the glass article has a thickness in the range of 20 μm to 150 μm and has a thickness defined by the following formula 2-1 and equal to or greater than 0.8*10 5 MPa / m 1.5 The first elastic energy index:
[0010] The first elastic energy index E elas1 =(1 / B)*Eabs (Formula 2-1),
[0011] Among them, "B" is brittleness, and "E abs ” is the absorbed energy and is defined by the following formula A:
[0012] Absorption energy E abs =σ 2 *(1-v) / E(Formula A)
[0013] Wherein, "σ" is the surface intensity and is defined by the following formula B:
[0014] Surface strength σ=(E*α*ρ 2 ) / (1-v)(Formula B)
[0015] where "E" is Young's modulus, "α" is the coefficient of thermal expansion, "ρ" is the density, and "v" is the Poisson's ratio, and
[0016] The stretch index β is defined by the following formula 2: KWW Equal to or greater than 0.95:
[0017]
[0018] Where "D" is the intensity factor, where D = B VFT / T 0 , "T 0 ” is the Vogel temperature, “T g ” is the glass transition temperature, and “B VFT "It is in T 0 The viscosity below.
[0019] The first elastic energy index may be equal to or greater than 0.9*10 5 MPa / m 1.5 .
[0020] The second elastic energy index defined by the following formula 2-2 may be equal to or greater than 0.1*10 -4 (kJ / m 2 ) 2 :
[0021] The second elastic energy index E elas2 =G IC *(1 / B) 6 *E abs (Formula 2-2),
[0022] Among them, "B" is brittleness, "E" is abs ” is the absorbed energy, and “G IC ” is the fracture energy index according to the following formula 1:
[0023] Fracture energy index G IC =(K IC 2 *(1-v 2 )) / E(Formula 1),
[0024] Among them, "K IC ” is the fracture toughness, “v” is the Poisson’s ratio, and “E” is the Young’s modulus.
[0025] The second elastic energy index may be equal to or greater than 0.12*10 -4 (kJ / m 2 ) 2 .
[0026] The fracture energy index can be equal to or greater than 150 kJ / m 2 .
[0027] The third elastic energy index defined by the following formula 2-3 may be equal to or greater than 2.1 MPa 2 / m 0.5 :
[0028] The third elasticity index E elas3 =G IC *(1 / B)*E abs (Formula 2-3)
[0029] Among them, "G IC ” is the fracture energy index, “B” is brittleness, and “E abs ” is absorbed energy.
[0030] The third elastic energy index may be equal to or greater than 2.3 MPa 2 / m 0.5 .
[0031] The crack generation height in the pen drop test performed with a pen whose ball diameter is 0.7 mm and whose weight is 1.12 g may be equal to or greater than 6 cm.
[0032] Glass products may contain SiO 2 、Al 2 O 3 and at least one metal oxide, the variable defined as the ratio of the content of the monovalent metal oxide to the content of the divalent metal oxide in the at least one metal oxide may be in the range of 7.0 to 8.5, and Al 2 O 3 The ratio of the content of to the total content of at least one metal oxide is in the range of 0.3 to 0.4.
[0033] According to an embodiment of the present disclosure, the glass article has a thickness in the range of 20 μm to 150 μm, and has a K value defined by the following formula 3-1 and equal to or greater than 0.001 K -1 The first free volume index:
[0034] The first free volume index V t1 =1 / T g (Formula 3-1),
[0035] Among them, "T g ” is the glass transition temperature, and
[0036] The stretch index β is defined by the following formula 2: KWW Equal to or greater than 0.95:
[0037]
[0038] Where "D" is the intensity factor, where D = B VFT / T 0 , "T 0 ” is the Vogel temperature, “T g ” is the glass transition temperature, and “B VFT "It is in T 0 The viscosity below.
[0039] The second free volume index defined by the following formula 3-2 may be equal to or greater than 7.0*10 -8 (kJ / m 2 ) 2 / K:
[0040] Second free volume index V t2 =G IC *(1 / B) 6 *E abs *(1 / T g )(Formula 3-2),
[0041] Among them, "T g ” is the glass transition temperature, “B” is brittleness, and “G IC ” is the fracture energy index defined by the following formula 1:
[0042] Fracture energy index G IC =(K IC 2 *(1-v 2 )) / E(Formula 1),
[0043] Among them, "K IC ” is the fracture toughness, “v” is the Poisson’s ratio, and “E” is the Young’s modulus,
[0044] “Eabs ” is the absorbed energy and is defined by the following formula A:
[0045] Absorption energy E abs =σ 2 *(1-v) / E(Formula A)
[0046] Wherein, "σ" is the surface intensity and is defined by the following formula B:
[0047] Surface strength σ=(E*α*ρ 2 ) / (1-v)(Formula B),
[0048] Wherein, "E" is Young's modulus, "α" is the coefficient of thermal expansion, "ρ" is the density, and "v" is the Poisson's ratio.
[0049] The second free volume index may be equal to or greater than 10.0*10 -8 (kJ / m 2 ) 2 / K.
[0050] The third free volume index defined by the following formula 3-3 may be equal to or greater than 6.0*10 -14 MPa 4 / (m 2.5 *K 3 ):
[0051] The third free volume index V t3 =G IC *(1 / B)*E abs *σ*(1 / (T g ) 3 )(Formula 3-3),
[0052] Among them, "T g ” is the glass transition temperature, “G IC " is the fracture energy index, "B" is brittleness, "E abs ” is the absorption energy, and “σ” is the surface strength.
[0053] The third free volume index may be equal to or greater than 9.0*10 -14 MPa 4 / (m 2.5 *K 3 ).
[0054] According to an embodiment of the present disclosure, a display device includes: a display panel including a plurality of pixels; a cover window disposed above the display panel; and an optically transparent bonding layer disposed between the display panel and the cover window. The cover window includes a glass product having a thickness in a range of 20 μm to 100 μm, and a first elastic energy index of the glass product is equal to or greater than 0.8*10 5MPa / m 1.5 , and is defined by the following formula 2-1:
[0055] The first elastic energy index E elas1 =(1 / B)*E abs (Formula 2-1),
[0056] Among them, "B" is brittleness, and "E abs ” is the absorbed energy and is defined by the following formula A:
[0057] Absorption energy E abs =σ 2 *(1-v) / E(Formula A),
[0058] Wherein, "σ" is the surface intensity and is defined by the following formula B:
[0059] Surface strength σ=(E*α*ρ 2 ) / (1-v)(Formula B),
[0060] where "E" is Young's modulus, "α" is the coefficient of thermal expansion, "ρ" is the density, and "v" is the Poisson's ratio, and
[0061] The first free volume index of the glass article is equal to or greater than 0.001K -1 , and is defined by the following formula 3-1:
[0062] The first free volume index V t1 =1 / T g (Formula 3-1),
[0063] Among them, "T g ” is the glass transition temperature, and
[0064] Glass product tensile index β KWW is equal to or greater than 0.95, and is defined by the following Formula 2:
[0065]
[0066] Where "D" is the intensity factor, where D = B VFT / T 0 , "T 0 ” is the Vogel temperature, “T g ” is the glass transition temperature, and “B VFT "It is in T 0 The viscosity below. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 is a perspective view of a glass article according to various embodiments.
[0068] Figure 2 is a perspective view of an unfolded display device incorporating a glass article according to an embodiment.
[0069] Figure 3 yes Figure 2 A perspective view of a folded display device.
[0070] Figure 4 is a cross-sectional view of an example in which a glass article according to an embodiment is used as a cover window of a display device.
[0071] Figure 5 is a cross-sectional view of a glass article having a flat plate shape according to an embodiment.
[0072] Figure 6 is a graph showing stress distribution of a glass article as a function of thickness according to an embodiment.
[0073] Figure 7 is a flow chart of a process for manufacturing a glass article according to an embodiment.
[0074] Figure 8 It is shown Figure 7 A diagram of the steps from the cutting step to the surface polishing step after strengthening.
[0075] Fig. 9 A pen drop test method for a glass product sample according to an embodiment is shown. DETAILED DESCRIPTION
[0076] Embodiments of the present disclosure will now be described more fully hereinafter with reference to the accompanying drawings. However, embodiments of the present disclosure may take different forms and should not be construed as limited to the embodiments set forth herein.
[0077] It will also be understood that when a layer is referred to as being 'on' another layer or substrate, it can be directly on the other layer or substrate, or intervening layers may also be present. The same reference numerals may refer to the same components throughout the specification.
[0078] Hereinafter, embodiments will be described with reference to the accompanying drawings.
[0079] Figure 1 is a perspective view of a glass article according to various embodiments.
[0080] Glass can be used as a cover window for protecting a display in an electronic device including a display (such as a tablet PC, a notebook PC, a smart phone, an e-book, a TV, and a PC display screen) and a refrigerator or a cleaning machine including a display screen, a substrate for a display panel, a substrate for a touch panel, an optical member such as a light guide plate, etc. Glass can also be used as a cover glass for a dashboard of a vehicle, a cover glass for a solar cell, an interior material for a building material, a window for a building and a house, etc.
[0081] Glass should have high strength. For example, when glass is used as a window, the glass should be thin to have high transmittance and light weight, and should also have strength to withstand external impact. Strengthened glass can be produced by, for example, chemical strengthening or thermal strengthening. Figure 1 Examples of tempered glass having various shapes are shown in FIG.
[0082] refer to Figure 1 In an embodiment, the glass article 100 may have a shape of a flat sheet or a flat plate. In other embodiments, the glass articles 101, 102, and 103 have a three-dimensional shape including a curved portion. For example, the edge of the flat portion may be curved, such as the glass article 101, or the flat portion may be integrally curved, such as the glass article 102, or the flat portion may be folded, such as the glass article 103. In other embodiments, the glass article 100 has a shape of a flat sheet or a flat plate and may be flexibly folded, stretched, or rolled.
[0083] The planar shape of the glass articles 100 to 103 may be a rectangular shape, but is not necessarily limited thereto, and may have various other shapes, such as a rectangular shape with rounded corners, a square shape, a circular shape, or an elliptical shape. In the embodiment, a flat plate having a rectangular planar shape is described as an example of the glass articles 100 to 103, but the embodiments of the present disclosure are not necessarily limited thereto.
[0084] Figure 2 is a perspective view of an unfolded display device incorporating a glass article according to an embodiment. Figure 3 It is shown Figure 2 A perspective view of a folded display device.
[0085] refer to Figure 2 and Figure 3 , the display device 500 according to the embodiment is a foldable display device. As will be described below, in the display device 500, Figure 1 The glass article 100 may be used as a cover window, and the glass article 100 may be flexible and / or foldable.
[0086] exist Figure 2 and Figure 3, the first direction DR1 is a direction parallel to the first side of the display device 500 in a plan view, and may be, for example, a horizontal direction of the display device 500. The second direction DR2 is a direction parallel to the second side in contact with the first side of the display device 500 in a plan view, and may be, for example, a vertical direction of the display device 500. The third direction DR3 is a thickness direction of the display device 500.
[0087] In an embodiment, the display device 500 has a rectangular shape in a plan view. The display device 500 has a rectangular shape with right angles or rounded corners in a plan view. The display device 500 includes two short sides extending in a first direction DR1 and two long sides extending in a second direction DR2 in a plan view.
[0088] The display device 500 includes a display area DA and a non-display area NDA. In a plan view, the shape of the display area DA corresponds to the shape of the display device 500. For example, when the display device 500 has a rectangular shape in a plan view, the display area DA also has a rectangular shape.
[0089] The display area DA includes a plurality of pixels that can display an image. The plurality of pixels are arranged in a matrix form. The plurality of pixels may have one of a rectangular, rhombus, and square shape in a plan view, but are not necessarily limited thereto. For example, the plurality of pixels may have a quadrilateral shape other than a rectangular, rhombus, or square shape, a polygonal shape other than a quadrilateral shape, a circular shape, or an elliptical shape.
[0090] The non-display area NDA does not include pixels and does not display an image. The non-display area NDA is disposed around the display area DA. The non-display area NDA surrounds the display area DA, but is not necessarily limited thereto. The display area DA may be partially surrounded by the non-display area NDA.
[0091] In an embodiment, the display device 500 can maintain both the folded state and the unfolded state. Figure 3 As shown, the display device 500 can be folded in an inward folding manner with the display area DA disposed inside thereof. When the display device 500 is folded inward, the top surfaces of the display device 500 face each other. For another example, the display device 500 can be folded in an outward folding manner with the display area DA disposed outside. When the display device 500 is folded outward, the bottom surfaces of the display device 500 face each other.
[0092] In an embodiment, the display device 500 is a foldable device. As used herein, the term "foldable device" means a device that can be folded, and not only means a folding device, but also means a device that can have both a folded state and an unfolded state. In addition, "folding" may include folding at an angle of about 180 degrees. However, the embodiments of the present disclosure are not necessarily limited thereto, and may include embodiments in which the folding angle exceeds 180 degrees or is less than 180 degrees, such as embodiments in which the folding angle is equal to or greater than 90 degrees and less than 180 degrees, or embodiments in which the folding angle is equal to or greater than 120 degrees and less than 180 degrees. In addition, the folded state may represent a state in which folding is performed from an unfolded state, even if full folding is not performed. For example, even if the display device 500 is folded at an angle of 90 degrees or less, as long as the maximum folding angle becomes 90 degrees or more, the display device 500 may also be presented as being in a folded state to distinguish it from an unfolded state. During folding, the radius of curvature may be 5 mm or less, or in the range of 1 mm to 2 mm, or about 1.5 mm, but is not necessarily limited thereto.
[0093] In an embodiment, the display device 500 includes a foldable area FDA, a first non-foldable area NFA1, and a second non-foldable area NFA2. The foldable area FDA is where the display device 500 is folded, and the first non-foldable area NFA1 and the second non-foldable area NFA2 are areas where the display device 500 is not folded.
[0094] The first non-foldable area NFA1 is disposed on one side (such as an upper side) of the foldable area FDA. The second non-foldable area NFA2 is disposed on the other side (such as a lower side) of the foldable area FDA. The foldable area FDA may be curved with a predetermined curvature.
[0095] In an embodiment, the foldable area FDA of the display device 500 is located at a specific position. In other embodiments, two or more foldable areas FDA are located at specific positions (multiple) in the display device 500. In another embodiment, the position of the foldable area FDA is not specific in the display device 500, but can be freely set in various areas.
[0096] In an embodiment, the display device 500 is folded in the second direction DR2. Therefore, the length of the display device 500 in the second direction DR2 is reduced to about half, so that the user can conveniently carry the display device 500.
[0097] In an embodiment, the direction in which the display device 500 is folded is not necessarily limited to the second direction DR2. For example, in an embodiment, the display device 500 may be folded in the first direction DR1. In this embodiment, the length of the display device 500 in the first direction DR1 is reduced to about half.
[0098] In the drawings, it is shown that each of the display area DA and the non-display area NDA overlaps with the foldable area FDA, the first non-foldable area NFA1, and the second non-foldable area NFA2, but the present disclosure is not limited thereto. For example, each of the display area DA and the non-display area NDA may overlap with at least one of the foldable area FDA, the first non-foldable area NFA1, and the second non-foldable area NFA2.
[0099] Figure 4 is a cross-sectional view of an example in which a glass article according to an embodiment is used as a cover window of a display device.
[0100] refer to Figure 4 In an embodiment, a display device 500 includes a display panel 200, a glass article 100 disposed on the display panel 200 and serving as a cover window, and an optically transparent bonding layer 300 disposed between the display panel 200 and the glass article 100 to bond the display panel 200 and the glass article 100 to each other.
[0101] Examples of the display panel 200 include not only self-luminous display panels (such as an organic light-emitting display (OLED) panel, an inorganic electroluminescent (EL) display panel, a quantum dot light-emitting display (QED) panel, a micro-LED display panel, a nano-LED display panel, a plasma display panel (PDP), a field emission display (FED) panel, or a cathode ray tube (CRT) display panel), but also light-receiving display panels (such as a liquid crystal display (LCD) panel or an electrophoretic display (EPD) panel).
[0102] The display panel 200 includes a plurality of pixels PX, and displays an image by using light emitted from each pixel PX. The display device 500 further includes a touch member. In an embodiment, the touch member is embedded in the display panel 200. For example, since the touch member is directly formed on the display member of the display panel 200, the display panel 200 itself can perform a touch function. In an embodiment, the touch member is manufactured separately from the display panel 200, and then attached to the top surface of the display panel 200 through an optically transparent bonding layer.
[0103] The glass article 100 is disposed above the display panel 200 and protects the display panel 200. Since the size of the glass article 100 is larger than that of the display panel 200, its side surface protrudes outward from the side surface of the display panel 200, but is not necessarily limited thereto. The display device 500 further includes a printed layer disposed on at least one surface of the glass article 100 at an edge portion of the glass article 100. The printed layer prevents a frame area of the display device 500 from being visible to the outside and may be decorative in some cases.
[0104] The optically transparent bonding layer 300 is disposed between the display panel 200 and the glass article 100. The optically transparent bonding layer 300 fixes the glass article 100 to the display panel 200. The optically transparent bonding layer 300 includes one or more of an optically clear adhesive (OCA), an optically clear resin (OCR), and the like.
[0105] Hereinafter, the strengthened glass article 100 will be described in more detail.
[0106] Figure 5 is a cross-sectional view of a glass article having a flat plate shape according to an embodiment.
[0107] refer to Figure 5 In an embodiment, the glass article 100 includes a first surface US, a second surface RS and a side surface SS (see Figure 1 In the flat plate-shaped glass article 100, the first surface US and the second surface RS have large areas, and the side surface SS (see Figure 1 ) is an outer surface connecting the first surface US and the second surface RS.
[0108] The first surface US and the second surface RS are opposite to each other in the thickness direction. When the glass article 100 transmits light like a cover window of a display, the light is mainly incident on one of the first surface US and the second surface RS and passes through to the other surface.
[0109] The thickness t of the glass article 100 is defined as the distance between the first surface US and the second surface RS. The thickness t of the glass article 100 may be 150 μm or less, or may be in the range of 20 μm to 150 μm, but is not necessarily limited thereto. In an embodiment, the thickness t of the glass article 100 is 100 μm or less. In an embodiment, the thickness t of the glass article 100 is 80 μm or less. In an embodiment, the thickness t of the glass article 100 is about 70 μm or less. In an embodiment, the thickness t of the glass article 100 is about 60 μm or less. In an embodiment, the thickness t of the glass article 100 is about 65 μm or less. In an embodiment, the thickness t of the glass article 100 is about 50 μm or less. In an embodiment, the thickness t of the glass article 100 is about 30 μm or less. In some embodiments, the thickness t of the glass article 100 is in the range of 20 μm to 50 μm, or is about 30 μm. In an embodiment, the glass article 100 has a uniform thickness t, but is not necessarily limited thereto, and other embodiments have a different thickness t for each region.
[0110] The glass article 100 is strengthened to have a predetermined stress profile. Compared with the unstrengthened glass article 100, the strengthened glass article 100 more effectively prevents the generation of cracks, the propagation of cracks, breakage, etc. due to external impact. The strengthened glass article 100 can have different stresses for each region. For example, near the surface of the glass article 100, such as near the first surface US and the second surface RS, compression regions CSR1 and CSR2 to which compressive stress is applied are formed, and a tensile region CTR to which tensile stress is applied is formed inside the glass article 100. The boundaries DOC1 and DOC2 between the compression regions CSR1 and CSR2 and the tensile region CTR have a stress value of zero. The compressive stress in one of the compression regions CSR1, CSR2 varies in its stress value according to a position, such as a depth from the surface. In addition, the tensile region CTR has different stress values according to the depth from the surface US, RS.
[0111] In the glass product 100, the positions of the compression regions CSR1 and CSR2, the stress distribution in the compression regions CSR1 and CSR2, the compression energy of the compression regions CSR1 and CSR2, the tensile energy of the tensile region CTR, etc. have a great influence on the mechanical properties (such as surface strength) of the glass product 100.
[0112] Figure 6 is a graph showing stress distribution as a function of thickness for a glass article according to one embodiment. Figure 6 In the graph of , the horizontal axis represents the thickness direction of the glass product. Figure 6In the equation, compressive stress has a positive value, while tensile stress has a negative value. The magnitude of compressive / tensile stress is independent of its sign and is the magnitude of its absolute value.
[0113] refer to Figure 6 In an embodiment, the glass article 100 includes a first compression region CSR1 extending from the first surface US to a first compression depth DOC1, and a second compression region CSR2 extending from the second surface RS to a second compression depth DOC2. The tensile region CTR extends between the first compression depth DOC1 and the second compression depth DOC2. The total stress distribution in the glass article 100 is symmetrical with respect to the center in the direction of the thickness t. Although Figure 6 Not shown in FIG. 1 , but compression and tension regions are similarly formed between opposing side surfaces of the glass article 100 .
[0114] The first compression region CSR1 and the second compression region CSR2 are resistant to external impacts and prevent cracks or breakage of the glass article 100. When the maximum compressive stresses CS1 and CS2 of the first compression region CSR1 and the second compression region CSR2 become larger after the strengthening process, the strength of the glass article 100 generally increases. Since external impacts are generally transmitted through the surface of the glass article 100, the maximum compressive stresses CS1 and CS2 should be at the surface of the glass article 100 in terms of durability. From this point of view, the compressive stresses of the first compression region CSR1 and the second compression region CSR2 tend to be maximum at the surface and generally decrease toward the inside.
[0115] The first compression depth DOC1 and the second compression depth DOC2 suppress the propagation of cracks or grooves formed in the first surface US and the second surface RS into the tensile region CTR in the glass article 100. Since the first compression depth DOC1 and the second compression depth DOC2 become larger after the strengthening process, the propagation of cracks, etc. can be more effectively prevented. The points corresponding to the first compression depth DOC1 and the second compression depth DOC2 correspond to the boundaries between the compression regions CSR1 and CSR2 and the tensile region CTR, and have a stress value of zero.
[0116] In the entire glass article 100, the tensile stress of the tensile region CTR is balanced with the compressive stress of the compressive regions CSR1 and CSR2. For example, the total compressive stress (such as the total compressive energy) in the glass article 100 is the same as the total tensile stress (such as the total tensile energy) in the glass article 100. The stress energy accumulated in the region of the glass article 100 having a constant width in the thickness t direction can be calculated as an integral value of the stress distribution. The following mathematical expression 1 represents the stress distribution in the glass article 100 having a thickness of t as a function f(x).
[0117] Mathematical expression 1:
[0118]
[0119] The greater the magnitude of the tensile stress in the glass article 100, the more likely the fragments are shattered when the glass article 100 breaks, and the more likely the glass article 100 is broken from the inside. The maximum tensile stress that satisfies the frangibility requirement of the glass article 100 satisfies, but is not necessarily limited to, the following Mathematical Expression 2.
[0120] Mathematical expression 2:
[0121] CT 1 ≤-38.7×ln(t)+48.2
[0122] In some embodiments, the maximum tensile stress CT1 is 100 MPa or less, or 85 MPa or less. A maximum tensile stress CT1 of 75 MPa or more improves mechanical properties such as strength. In an embodiment, the maximum tensile stress CT1 is greater than or equal to 75 MPa and less than or equal to 85 MPa, but is not necessarily limited thereto.
[0123] The maximum tensile stress CT1 of the glass article 100 is located substantially at the central portion in the thickness t direction of the glass article 100. For example, the maximum tensile stress CT1 of the glass article 100 is located at a depth in the range of 0.4t to 0.6t, or at a depth in the range of 0.45t to 0.55t, or at a depth of about 0.5t.
[0124] In addition, in order to increase the strength of the glass article 100, the compressive stress and the compression depths DOC1 and DOC2 should have large values. However, as the compression energy increases, the tensile energy also increases, and the maximum tensile stress CT1 increases. In order to meet the fragility requirements while having high strength, the stress distribution should be adjusted so that the maximum compressive stresses CS1 and CS2 and the compression depths DOC1 and DOC2 have large values while the compression energy is reduced. To this end, the glass article 100 is manufactured using a glass composition containing a predetermined content of a specific component. According to the composition ratio of each component in the glass composition, the manufactured glass article 100 has excellent strength, flexibility and physical properties so as to be incorporated into a foldable display device.
[0125] According to an embodiment, the glass composition of the glass article 100 includes SiO 2 、Al 2 O 3 、Na 2 O. Li 2 O, CaO or MgO and ZrO 2 One or more of .
[0126] SiO 2 It constitutes the skeleton of glass, increases chemical durability and reduces the generation of cracks when scratches (indentations) are formed on the glass surface. SiO 2 Forming a glass network, and containing SiO 2 The manufactured glass article 100 has a reduced coefficient of thermal expansion and increased mechanical strength.
[0127] Al 2 O 3 Improves the breakage resistance of glass. For example, when glass breaks, Al 2 O 3 Produces less debris. 2 O 3 Is with SiO 2 The intermediate oxides that form bonds to form a network structure. In addition, Al 2 O 3 It is an active component that improves ion exchange properties during chemical strengthening and increases surface compressive stress after strengthening.
[0128] Na 2 O forms surface compressive stress through ion exchange and increases the solubility of the glass. 2 O forms a network structure with SiO 2 The oxygen forms ionic bonds in SiO 2 Non-bridging oxygen is formed in the network structure. The increase of non-bridging oxygen increases the flexibility of the network structure, and the glass article 100 has physical properties suitable for a foldable display device.
[0129] As described above, Na 2 O is similar to Li 2 O forms surface compressive stress through ion exchange and increases the solubility of the glass. 2 O forms a network structure with SiO 2 The oxygen forms ionic bonds and 2 Non-bridging oxygen is formed in the network structure. The increase of non-bridging oxygen can increase the flexibility and impact absorption function of the network structure, and the glass article 100 has physical properties suitable for a foldable display device.
[0130] MgO increases the surface strength of glass and lowers the temperature at which glass forms. MgO is a strong 2 The network modifier oxide is used to modify the network structure. MgO reduces the refractive index of the glass and adjusts the thermal expansion coefficient and elastic modulus of the glass. CaO increases the surface strength of the glass. CaO is a network modifier for SiO 2A network modifier oxide that modifies the network structure. CaO increases the glass transition temperature of the glass and improves chemical durability.
[0131] ZrO 2 Increases the transmittance and surface strength of glass and increases resistance to surface crack propagation. ZrO 2 It is SiO that forms a network structure 2 An intermediate oxide that forms a bond. ZrO 2 With SiO 2 The network structure is composed of Li 2 O and Na 2 O combines broken bonds to increase the fracture toughness of the glass and increase repulsive force against bending.
[0132] In addition to the above-mentioned components, the glass composition may also include, as required, 2 O 5 , B 2 O 3 , K 2 O, Y 2 O 3 ,La 2 O 3 , Nb 2 O 5 、 2 O 5 or Gd 2 O 3 In addition, it can also include a small amount of Sb 2 O 3 、CeO 2 SnO 2 and / or As 2 O 3 As a clarifying agent.
[0133] The glass article 100 manufactured using the glass composition according to the embodiment has characteristics and physical properties suitable for a foldable display device. For example, the glass article 100 is flexible to fold and unfold, and has strength and chemical properties suitable for use as a cover window of the display device 500. In addition, the glass composition is flexible so that the glass article 100 can be folded and unfolded. The folding and unfolding characteristics of the glass article 100 are improved by reducing the glass transition temperature and elastic modulus of the glass. For example, when the elastic modulus of the glass is reduced, the stress applied to the lower part of the glass article during folding and unfolding is reduced, thereby increasing the bending characteristics of the glass article. In addition, the impact resistance can be improved by reducing the elastic modulus, which is inversely proportional to the probability of molecular vibration in the case of impact, and increasing the free volume fraction, which is proportional to the impact energy.
[0134] The glass article 100 according to the embodiment can be made by using the glass composition as follows: Figure 7 and Figure 8 The glass article 100 is further subjected to a quenching process and a strengthening process in the manufacturing process described below to have improved impact resistance. The physical properties of the glass article 100 related to the intermolecular bonding strength can be enhanced according to the type and composition ratio of the components of the glass composition. In addition, the physical properties of the glass article 100 such as density, fracture toughness and brittleness can be further enhanced by the quenching process, and the physical properties of the glass article 100 such as strengthening stress, glass transition temperature related to stress depth, Young's modulus, density, hardness and brittleness can be further enhanced by the chemical strengthening process. The glass article 100 according to the embodiment has excellent impact resistance due to the quenching process and strengthening process performed during the manufacturing process, and has, for example, physical properties and characteristics suitable for the foldable display device 500.
[0135] The glass composition having the above ingredients can be molded into a plate glass shape by various methods known in the art. When the glass composition is molded into a plate glass shape, the glass composition can be further processed and manufactured into a glass product 100 suitable for the display device 500. However, the embodiments of the present disclosure are not necessarily limited thereto, and the glass composition may not be molded into a plate glass shape and may be directly molded into a glass product 100 suitable for a product without an additional molding process.
[0136] Hereinafter, a method of molding the glass composition into a plate glass shape and processing it into the glass article 100 will be described.
[0137] Figure 7 is a flow chart of steps of a process for making a glass article according to an embodiment. Figure 8 It is shown Figure 7 A diagram of the steps from the cutting step to the surface polishing step after strengthening.
[0138] refer to Figure 7 and Figure 8 In an embodiment, the method for manufacturing the glass article 100 includes a molding step S1, a cutting step S2, a side polishing step S3, a surface polishing step before strengthening S4, a strengthening step S5, and a surface polishing step after strengthening S6.
[0139] The molding step S1 includes preparing a glass composition and molding the glass composition. The glass composition has the ingredients and components as described above, and therefore a repeated detailed description thereof is omitted. The glass composition is molded into a plate glass shape by a method such as a float process, a fusion draw process, or a slot draw process.
[0140] The glass molded into a flat plate shape is cut in the cutting step S2. The glass molded into a flat plate shape has a size different from that of the final glass product 100. For example, glass molding is performed to form a large-area substrate as a mother glass substrate 10a including a plurality of glass products. The mother glass substrate 10a is cut into a plurality of units (e.g., a plurality of glasses 10) to produce a plurality of glass products. For example, even if the final glass product 100 has a size of about 6 inches, when the glass is molded into a size several to hundreds of times larger (e.g., 120 inches) and then cut, 20 glass products molded into a flat plate shape are obtained at one time. In this way, process efficiency is improved compared to molding a single glass product separately. In addition, even when molding glass corresponding to the size of one glass product, if the final glass product has one of various planar shapes, it can be made into a desired shape by a cutting process.
[0141] The cutting of the mother glass substrate 10 a is performed using a cutting blade 20 , a cutting wheel, a laser, or the like.
[0142] The cutting step S2 is performed before the strengthening step S5. The mother glass substrate 10a may be strengthened once and then cut into the size of the final glass product. However, in this case, the cut surface (such as the side surface of the glass) is placed in a non-strengthened state. Therefore, the strengthening step S5 is performed after the cutting is completed.
[0143] Between the cutting step S2 and the strengthening step S5 of the glass, a polishing step before strengthening is performed. The polishing step includes a side polishing step S3 and a surface polishing step before strengthening S4. In an embodiment, after the side polishing step S3 is performed, the surface polishing step before strengthening S4 is performed, but the embodiment is not necessarily limited thereto, and in an embodiment, the order is reversed.
[0144] The side polishing step S3 polishes the side surface of the cut glass 10. In the side polishing step S3, the side surface of the glass 10 is polished to have a smooth surface. In addition, each side surface of the glass 10 has a uniform surface through the side polishing step S3. For example, the cut glass 10 includes one or more cut surfaces. In some cut glasses 10, two of the four side surfaces are cut surfaces. In some other cut glasses 10, three of the four side surfaces are cut surfaces. In some other cut glasses 10, all four side surfaces are cut surfaces. When the side surface is a cut surface, it has a surface roughness different from the surface roughness of the non-cut surface. In addition, even if it is a cut surface, it can also have different surface roughness. Therefore, by polishing each side surface via the side polishing step S3, each side surface has a uniform surface roughness, etc. In addition, small cracks that may exist on the side surface are removed by the side polishing step S3.
[0145] The side polishing step S3 may be simultaneously performed on a plurality of cut glasses 10. For example, when a plurality of cut glasses 10 are stacked, the stacked glasses 10 may be polished at the same time.
[0146] The side polishing step S3 may be performed by one of a mechanical polishing method or a chemical mechanical polishing method using the polishing device 30. In an embodiment, two opposite side surfaces of the cut glass 10 are polished simultaneously, and then another two opposite side surfaces are polished simultaneously, but embodiments of the present disclosure are not necessarily limited thereto.
[0147] The surface polishing step S4 before strengthening is performed so that each glass 10 has a uniform surface. The surface polishing step S4 before strengthening may be performed individually for each cut glass 10. However, when the chemical mechanical polishing apparatus 40 is sufficiently large compared to the glass 10, a plurality of glasses 10 are horizontally arranged and then surface polished simultaneously.
[0148] The surface polishing step S4 before strengthening is performed by chemical mechanical polishing. For example, the first surface and the second surface of the cut glass 10 are polished using a chemical mechanical polishing device 40 and a polishing slurry. In an embodiment, the first surface and the second surface are polished at the same time. In an embodiment, one of the first surface and the second surface is polished, and then the other surface is polished.
[0149] After the surface polishing step S4 before strengthening, the strengthening step S5 is performed. The strengthening step S5 includes chemical strengthening and / or thermal strengthening. When the glass 10 has a thickness of 2 mm or less (such as about 0.75 mm or less), the chemical strengthening method is appropriately used for precise stress distribution control.
[0150] After the strengthening step S5, optionally, a post-strengthening surface polishing step S6 is further performed. The post-strengthening surface polishing step S6 removes fine cracks on the surface of the strengthened glass 10 and controls the compressive stress of the first surface and the second surface of the strengthened glass 10. For example, a floating method is performed by flowing a glass composition into a tin bath, which is one of the methods for manufacturing a glass sheet. For example, the surface of the glass sheet that is in contact with the tin bath has a different composition from the surface that is not in contact with the tin bath. As a result, after the strengthening step S5 of the glass 10, a deviation in compressive stress may occur between the surface that is in contact with the tin bath and the surface that is not in contact with the tin bath. However, by polishing to remove the surface of the glass 10 to an appropriate thickness, the deviation in compressive stress between the contact surface and the non-contact surface can be reduced.
[0151] The post-strengthening surface polishing step S6 is performed by a chemical mechanical polishing method. For example, the first surface and the second surface of the strengthened glass 10 are polished using a chemical mechanical polishing device 60 and a polishing slurry. The polishing thickness can be adjusted to be within a range of, for example, 100 nm to 1000 nm, but is not necessarily limited thereto. The polishing thickness of the first surface and the second surface may be the same, or may be different.
[0152] In addition, after the surface polishing step S6 after strengthening, a further shape processing process can be performed as needed. Figure 1 When the three-dimensionally shaped glass products 101 to 103 are shown, a three-dimensional processing process is performed after the surface polishing step S6 after strengthening.
[0153] As described above, the glass article 100 manufactured by the above process can be used as a cover window of the foldable display device 500. The glass article 100 is flexible and foldable. In addition, the glass article 100 has impact resistance characteristics suitable for use as a cover window.
[0154] The impact resistance of the glass article 100 is related to various mechanical and chemical properties of the glass article 100. For example, the glass article 100 has properties such as thermal expansion coefficient, transition temperature, density, Young's modulus, Poisson's ratio, Vickers hardness, fracture toughness, brittleness, etc. In a sample of the glass article 100, the physical properties are measurable. Generally, when the value of the physical property exceeds the characteristic level, the glass article 100 has excellent impact resistance, but its reference value may be unclear. For example, when comparing the physical properties of various glass articles 100, it may be challenging to determine whether a glass article 100 having a relatively high value of a specific physical property must have better external impact resistance than other glass articles 100. This means that it is necessary to comprehensively evaluate various physical properties of the glass article 100 to determine whether it has excellent impact resistance, and the impact resistance of the glass article 100 may not be determined by the measurable physical properties of the glass article 100. For example, when the glass article 100 is used as a cover window of the display device 500 , the correlation between the impact resistance characteristics of the glass article 100 and the values of the physical properties of the glass article 100 may not be clear.
[0155] The pen drop test may be used as one of the indicators for evaluating the impact resistance of the glass article 100. When various glass articles 100 are prepared as samples and the pen drop test is performed, the impact resistance of the glass article 100 may be determined by the height of the pen at which cracks or damage begin to appear in the glass article sample. For example, compared to the value of the physical property of the glass article 100, the pen drop test result may be a better standard for evaluating the impact resistance of the glass article 100.
[0156] In addition, whether the glass article 100 is damaged is affected by upper and lower damage in the region where the impact is applied and structural changes of molecules constituting the glass article 100. If the glass article 100 has high resistance to upper and lower damage, the glass article 100 may withstand the external impact. If there is a free space between the molecules constituting the glass article 100, the molecular structure can be easily changed, and the glass article 100 may withstand the external impact.
[0157] The main factors of the damage resistance and molecular structure of the glass article 100 are the fracture energy and elastic energy of the glass article 100, and the free volume obtained therefrom. The fracture energy and elastic energy include the physical properties of the glass article 100 described above as the main factors, and the free volume includes the fracture energy and elastic energy as the main factors. In the glass article 100, factors related to the fracture energy, elastic energy, and the free volume obtained from the physical properties described above may be defined.
[0158] According to an embodiment, the glass article 100 has factors that can be quantified and derived as measurable physical properties, and the quantified factors are consistent with pen drop test results that are clear standards of impact resistance. Therefore, the pen drop test results and impact resistance of the glass article 100 are determined by the values of specific factors, and the impact resistance of the glass article 100 can be increased by adjusting the values of the corresponding factors. The glass article 100 has an increased pen drop property, that is, impact resistance, because a specific factor to be described below has a specific value or more. Hereinafter, various factors consistent with the pen drop test results include factors that can be obtained from measurable physical properties of the glass article 100.
[0159] The fracture energy index of the glass article 100 , which is a factor of bonding strength or resistance to upper damage against external impact, may be defined by Formula 1 below.
[0160] Fracture energy index (G IC )=(K IC 2 *(1-v 2 )) / E(kJ / m 2 )(Formula 1)
[0161] In Formula 1, “K IC ” is the fracture toughness, “v” is the Poisson’s ratio, and “E” is the Young’s modulus. The fracture energy index G in Formula 1 IC The unit is "kJ / m 2 "K IC ", "v" and "E" values can be expressed in "kJ / m 2 " is expressed as a unit.
[0162] The fracture energy index of the glass article 100 is a factor related to the resistance to upper damage caused by external impact. The fracture energy index increases as the fracture toughness increases and the Poisson's ratio and Young's modulus decrease. For example, as the fracture toughness increases and the Poisson's ratio and Young's modulus decrease, the glass article 100 has an increased fracture energy index value, as well as increased bonding strength and resistance to upper damage caused by external impact. For example, the glass article 100 has a fracture energy index value of 150 kJ / m according to Formula 1. 2 or greater fracture energy index.
[0163] According to an embodiment, the first elastic energy index of the glass article 100 is defined by the following Formula 2-1.
[0164] The first elastic energy index (E elas1 )=(1 / B)*E abs (MPa / m 1.5 )(Formula 2-1)
[0165] In formula 2-1, "B" is brittleness (fracture toughness K IC / Hardness H v m 0.5 ), "E abs " is the absorbed energy, and the unit of the first elastic energy index may be "MPa / m 1.5 In formula 2-1, "B" and "E abs "Value in MPa / m 1.5 " is expressed as a unit.
[0166] “E abs ”, which is the absorption energy in Formula 2-1, is defined by the following Formula A.
[0167] Absorption energy (E abs )=σ 2 *(1-v) / E(MPa / m 2 )(Formula A)
[0168] In Formula A, "σ" is surface intensity, and is defined by Formula B below.
[0169] Surface strength (σ) = (E*α*ρ 2 ) / (1-v)(MPa / m) 2 (Formula B)
[0170] In Formula B, "E" is Young's modulus, "α" is the thermal expansion coefficient, "ρ" is the density, and "v" is the Poisson's ratio.
[0171] The elastic energy index of the glass article 100 is related to the resistance to lower bending damage caused by external impact. As the brittleness decreases and the absorbed energy increases, the first elastic energy index has a higher value. For example, according to Formula A and Formula B, the first elastic energy index of the glass article 100 increases as the surface strength increases, the brittleness decreases, and the absorbed energy increases.
[0172] As described above, the glass article 100 may be manufactured by performing a quenching process and a chemical strengthening process during a manufacturing process using the glass composition. The glass article 100 subjected only to the quenching process has physical properties different from those of the glass article 100 subjected to both the quenching process and the chemical strengthening process. In an embodiment, the first elastic energy index of the glass article 100 manufactured by performing the quenching process is 0.9*10 5 MPa / m 1.5 In an embodiment, the first elastic energy index of the glass article 100 manufactured by performing the quenching process and the chemical strengthening process is 0.8*10 5 MPa / m 1.5 or larger.
[0173] According to an embodiment, other factors consistent with the pen drop test result regarding the first elastic energy index of the glass article 100 may be defined. The second elastic energy index and the third elastic energy index of the glass article 100 are defined by the following Formula 2-2 and Formula 2-3, respectively.
[0174] The second elastic energy index (E elas2 )=G IC *(1 / B) 6 *E abs (kJ / m 2 ) 2 (Formula 2-2)
[0175] The third elastic index (E elas3 )=G IC *(1 / B)*E abs (MPa 2 / m 0.5 )(Formula 2-3)
[0176] In Formula 2-2 and Formula 2-3, "G IC " is the fracture energy index according to Formula 1. The second elastic energy index and the third elastic energy index of Formula 2-2 and Formula 2-3 include the fracture energy index G of Formula 1 in the first elastic energy index IC The second elastic energy index E elas2 and the third elastic energy index E elas3 The glass product has an elastic index E of 100 at the first elas1 The pen drop test in the same.
[0177] In an embodiment, the second elastic energy index of the glass article 100 manufactured by performing the quenching process is 0.12*10 -4 (kJ / m 2 ) 2 or greater, and its third elastic energy index is 2.3MPa 2 / m 0.5 In an embodiment, the second elastic energy index of the glass article 100 manufactured by performing the quenching process and the chemical strengthening process is 0.1*10 -4 (kJ / m 2 ) 2 or greater, and its third elastic energy index is 2.1 MPa 2 / m 0.5 or larger.
[0178] According to an embodiment, the glass article 100 has a first free volume index defined by the following Formula 3-1.
[0179] The first free volume index (V t1 )=1 / T g (K-1 )(Formula 3-1)
[0180] In formula 3-1, “T g ” is the glass transition temperature. The first free volume index V of formula 3-1 t1 The unit can be "K -1 ”.
[0181] The free volume index of the glass article 100 is related to the molecular vibration and molecular structure of the glass article 100 for external impact. A first free volume index V related to the molecular structure of the glass article 100 t1 has a value that decreases as the glass transition temperature increases. When the glass article 100 has a large amount of space between molecules due to its molecular structure, for example, when the free volume is large, the molecular structure is not changed by external impact, and the glass article 100 has excellent crack resistance to external impact. However, this relationship involves a balance between the bonding strength and density of the glass article 100. In an embodiment, the first free volume index V of the glass article 100 manufactured by performing the quenching process is t1 and a first free volume index V of the glass article 100 manufactured by performing the quenching process and the chemical strengthening process t1 0.001K -1 or larger.
[0182] According to an embodiment, other factors consistent with the pen drop test result regarding the first free volume index may be further defined for the glass article 100. The second free volume index and the third free volume index of the glass article 100 may be defined by the following Formulas 3-2 and 3-3, respectively.
[0183] The second free volume index (V t2 )=G IC *(1 / B) 6 *E abs *(1 / T g )((kJ / m 2 ) 2 / K)
[0184] (Formula 3-2)
[0185] The third free volume index (V t3 )=G IC *(1 / B)*E abs *σ*(1 / (T g ) 3 )(MPa 4 / (m 2.5 *K 3 ))
[0186] (Formula 3-3)
[0187] In Formula 3-2 and Formula 3-3, “T g ” is the glass transition temperature, “G IC " is the fracture energy index, "B" is brittleness, "E abs " is the absorption energy, and "σ" is the surface intensity. The second free volume index V of formula 3-2 t2 The unit is (kJ / m 2 ) 2 / K, and the third free volume index V of formula 3-3 t3 The unit is MPa 4 / (m 2.5 *K 3 ).
[0188] The second free volume index and the third free volume index of Formula 3-2 and Formula 3-3 are related to the second elastic energy index and the third elastic energy index of Formula 2-2 and Formula 2-3 in the first free volume index. t2 and the third free volume index V t3 Each of the glass articles 100 has a first free volume index V t1 In an embodiment, the second free volume index V of the glass article 100 manufactured by performing the quenching process is consistent with the pen drop test in FIG. t2 10.0*10 -8 (kJ / m 2 ) 2 / K or greater, and its third free volume index V t3 9.0*10 -14 MPa 4 / (m 2.5 *K 3 ) or greater. In an embodiment, the second free volume index V of the glass article 100 manufactured by performing the quenching process and the chemical strengthening process is t2 7.0*10 -8 (kJ / m 2 ) 2 / K or greater, and its third free volume index V t3 6.0*10 -14 MPa 4 / (m 2.5 *K 3 ).
[0189] Formula 1, Formula 2-1 to Formula 2-3, and Formula 3-1 to Formula 3-3 described above are respectively related to the fracture energy, elastic energy, and free volume of the glass article 100. However, the "fracture energy index", "elastic energy index", and "free volume index" of the glass article 100 in the present disclosure may be defined by the formulas described above, and may not be completely equivalent to the formulas of "fracture energy", "elastic energy", and "free volume" commonly used in the technical field of the present disclosure. The "fracture energy index", "elastic energy index", and "free volume index" defined in the above formulas may be defined by partially modified formulas consistent with the pen drop test of the impact resistance of the glass article 100.
[0190] The glass article 100 according to the embodiment has a thickness of 100 μm or less, for example, 20 μm to 100 μm or about 30 μm, and the fracture energy index, elastic energy index, and free volume index according to Formula 1, Formula 2-1 to Formula 2-3, and Formula 3-1 to Formula 3-3 satisfy the values within the range described above.
[0191] The glass article 100 is thin and foldable, and therefore requires a high level of impact resistance. As described above, each of the measurable physical properties of the glass article 100 may not be consistent with the pen drop test results and the impact resistance of the glass article 100. For example, even if a specific physical property of the glass article 100 has a high value, the glass article 100 may not necessarily have excellent impact resistance. However, according to an embodiment, the factors defined by Formula 1, Formula 2-1 to Formula 2-3, and Formula 3-1 to Formula 3-3 include measurable physical properties of the glass article 100 that are consistent with the pen drop test results. Therefore, the degree of impact resistance of the glass article 100 can be measured by the quantitative factors of the glass article 100.
[0192] In addition, the glass article 100 according to the embodiment has characteristics suitable for the cover window of the foldable display device 500. The glass article 100 has the impact resistance characteristics and the small thickness described above, and satisfies the transparency, the content of foreign matter or cracks in a unit area, and the light transmittance, which are sufficient for the glass article 100 to be incorporated into the display device 500. The glass article 100 has the impact resistance characteristics because the brittleness index described above satisfies a specific value, and has the physical properties or characteristics required for the cover window of the display device 500 to provide a transparent screen to the user.
[0193] According to an embodiment, the glass article 100 has a tensile index β equal to or greater than 0.95 (eg, in the range of 0.95 to 1.00). KWW. The glass article 100 is suitable for use as a cover window for a foldable display device because it has excellent impact resistance while satisfying the brittleness index described above and has a high tensile index. The "tensile index" is a physical property related to the strength factor, the Vogel temperature, and the glass transition temperature, and indicates the mobility and activity of atoms in the glass structure, and verifies the structural flow of the glass network structure. Since the glass article 100 has a high tensile index, it has excellent structural flow and flexible product characteristics.
[0194] Furthermore, as mentioned above, in addition to SiO 2 and Al 2 O 3 In addition, the glass article 100 also includes Na 2 O. Li 2 O, CaO or MgO and ZrO 2 The physical properties of the glass product 100 are determined according to the content of the metal oxide in the glass product 100 and the Al 2 O 3 According to the embodiment, in the glass article 100, the monovalent metal oxide R 1 2 O (where "R 1 ” is a monovalent metal element) and the content of divalent metal oxide R 2 O (where "R 2 ” is the content ratio of divalent metal elements) (R 1 2 O / R 2 The flux of A1 is in the range of 5 to 10 (e.g., in the range of 7.0 to 8.5), and is defined as 2 O 3 The content of metal oxides (R 1 2 O+R 2 O) ratio (Al 2 O 3 / (R 1 2 O+R 2 O)) has an R-Ratio (R-ratio) in the range of 0.2 to 0.6 (e.g., in the range of 0.3 to 0.4). In the above formula, “R 1 ” and “R 2 " is a monovalent metal element or a divalent metal element, and "R 1 2 O" and "R 2 Examples of O" include Na 2O. Li 2 O.K 2 O, CaO, MgO, etc. The glass article 100 has the brittleness index, high tensile index, and variables having specific values as described above, and the R-ratio has a value within the above-described range, and thus has excellent impact resistance and flexibility.
[0195] Hereinafter, the results of the pen drop test performed on various glass articles 100 and the consistency evaluation between the above-mentioned factors will be described.
[0196] Example
[0197] Preparation Example 1: Preparation of glass product samples
[0198] A plurality of glass substrates having various compositions were prepared and divided into Sample #1 to Sample #21, and then, a glass article preparation process was performed on each sample by the above-described method. A glass article specimen for each sample was prepared to have a thickness of 50 μm.
[0199] Samples of glass product specimens were prepared by the following method.
[0200] The glass product samples were molded into glass blocks by: weighing 500 g of the glass product sample using a PtRh10% crucible for each sample; increasing the temperature from 1500°C to 1650°C at a rate of 10 K / min; maintaining the temperature for 3 to 6 hours; and rapidly cooling it to 600°C in a carbon mold.
[0201] In order to remove residual stress of the prepared glass block, annealing was performed at a temperature 30° C. higher than the glass transition temperature for each sample for 1 to 6 hours, and then, the glass block was cooled to 400° C. at a rate of 1 K / min, and then cooled to room temperature, thereby obtaining a glass block having a thickness of 10 mm.
[0202] In order to perform a pen drop test on the prepared glass block, the glass block was cut into a thickness of 270 μm using a diamond wire saw equipment, and then polished on both sides until the thickness became 50 μm.
[0203] Using KNO 3 Molten salt chemically strengthens the samples processed into 50 μm for each sample. The surface compressive stress (CS) is controlled in the range of 700 MPa to 800 MPa, and the depth of layer (DoL) is controlled in the range of 15% to 20% compared to the glass thickness. However, some samples were subjected to the pen drop test without undergoing the chemical strengthening process.
[0204] In order to compare the factors defined by the above formula with the actual pen drop test results of the glass product samples, the structural flow of the glass product samples was examined by theoretical viscosity calculation, and the main factors of impact resistance were examined by physical property analysis. First, the viscosity of the glass was examined by the Vogel–Fulcher–Tammann (VFT) formula, and the following formula (1) is related to the viscosity and temperature of the glass.
[0205]
[0206] Where η is the viscosity, A VFT is the high temperature limiting viscosity, T 0 is the Vogel temperature, and B VFT It is in T 0 The viscosity below.
[0207] In order to examine the flow of the glass structure based on the Vogel temperature, the following equation (2) is obtained based on the Kohlrausch-Williams-Watts (KWW) formula.
[0208]
[0209] Here, β KWW is the tensile index, D is the strength factor (=B VFT / T 0 ), T 0 is the Vogel temperature, and T g is the glass transition temperature. Vogel temperature T 0 is the ideal glass transition temperature T g , and roughly represents the point at which the free volume required for the relaxation of the glass network structure is theoretically zero regardless of manufacturing conditions (such as cooling rate, volume, and defects in the glass sample). Therefore, the viscosity of the formed glass network structure can be determined by Vogel temperature comparison. In addition, by T 0 Calculated stretch index β KWW Indicates the mobility and activity of atoms in the glass structure and verifies the structural flow of the glass network.
[0210] Next, the physical properties of the glass product samples for each sample were measured and compared with the Vogel temperature T 0 and the stretching index β KWW The measured physical properties of the glass product samples include the coefficient of thermal expansion CTE, the glass transition temperature T g , density ρ, Young's modulus E, Poisson's ratio v, hardness H v , fracture toughness K IC and brittle B.
[0211] The glass transition temperature T was checked by preparing 5 g for each glass sample using a differential thermal analysis (DTA) equipment and increasing the temperature to the glass transition temperature range at a rate of 10 K / min. g A 10×10×13 mm2 thermomechanical analyzer (TMA) was used to prepare a 10×10×13 mm2 thermomechanical analyzer (TMA) for each component. 3 The thermal expansion coefficient of the glass is tested by taking a sample of the size of and raising the temperature to the glass transition temperature range at a rate of 10K / min.
[0212] By manufacturing each component with a size of 10×20×3mm 3 The Poisson's ratio was tested by measuring the stress and strain of the samples using an elastic modulus tester.
[0213] Hardness H v and fracture toughness K IC The hardness was calculated by the following equations (3) and (4) by applying a load of 4.9 N for 30 seconds using a Vickers hardness tester equipped with a diamond tip having a size of 19 μm.
[0214]
[0215] Among them, H V indicates Vickers hardness, F indicates load, and a indicates indentation length.
[0216]
[0217] Among them, K IC indicates fracture toughness, Φ indicates constraint index (φ≈3), H V indicates Vickers hardness, K indicates a constant (=3.2), c indicates a crack length, and a indicates an indentation length.
[0218] The brittleness (B) was calculated by the following formula (5) by applying a load of 4.9 N for 30 seconds using a Vickers hardness tester equipment.
[0219]
[0220] Where B is brittleness and γ is a constant (2.39N 1 / 4 / μm 1 / 2 ), P is the indentation load, a is the indentation length, and C is the crack length.
[0221] The crack initiation load was measured using a Vickers hardness tester setup.
[0222] Table 1
[0223]
[0224]
[0225] In this table, “CTE” is the coefficient of thermal expansion, and “T g ” is the glass transition temperature, “ρ” is the density, “E” is the Young’s modulus, “v” is the Poisson’s ratio, and “H v ” is the hardness, and “K IC ” is fracture toughness, and “B” is brittleness.
[0226] Test Example 1: Impact resistance evaluation - pen drop (pen diameter 0.7 mm) evaluation
[0227] The glass product sample prepared in Preparation Example 1 was used to perform the following Fig. 9 Pen Drop Test (PDT) shown. A Pen Drop Test was performed using glass article samples that were subjected to both a quenching process and a chemical strengthening process.
[0228] Fig. 9 A pen drop test method for a glass product sample according to an embodiment is shown.
[0229] refer to Fig. 9 In an embodiment, a glass product sample GP having a thickness of 50 μm is prepared and bonded to a polyethylene film substrate SUB having a thickness of 250 μm. After the glass product sample GP and the polyethylene film substrate SUB are bonded and cured for more than 30 minutes, a pen drop test is performed. The pen drop test is performed by dropping a pen PEN having a ball diameter of 0.7 mm and a weight of 1.12 g at a temperature of 20° C. to 22° C. and a humidity of 30% using an automatic drop device ADB until a crack appears in the glass product sample GP. The drop height H is increased at intervals of 0.5 cm using a drop height control device HCS, and the glass product sample GP is observed through a microscope after one impact to check whether cracks or cracks have occurred. The drop height H is defined as the vertical distance from the glass product sample GP to the drop height control device HCS.
[0230] The pen drop test was performed 30 times on three or more of the same glass product samples GP, and the average value was measured and shown in the following Table 2. In addition, the physical properties measured in Preparation Example 1, the elastic energy index and the free volume index defined in Formula 2-1 to Formula 2-3 and Formula 3-1 to Formula 3-3, and the tensile index were calculated and shown in the following Table 2. The fracture energy index, the elastic energy index, and the free volume index shown in the following Table 2 are values of the glass product samples subjected to both the quenching process and the chemical strengthening process.
[0231] Table 2
[0232]
[0233] In Table 2, the glass product samples are sorted in the order of the pen drop test (PDT) results. In the pen drop test, sample #1 has excellent impact resistance due to crack generation at the highest position, and sample #21 has poor impact resistance due to crack generation at the lowest position. In an embodiment, the crack generation height in the pen drop test performed with a pen having a ball diameter of 0.7 mm and a weight of 1.12 g may be equal to or greater than 6 cm.
[0234] With reference to Table 2, the pen drop test results and the values of Formulas 2-1 to 2-3 and 3-1 to 3-3 show substantially the same trend. Samples having small values of Formulas 2-1 to 2-3 and 3-1 to 3-3 substantially have poor pen drop test results. For example, if the fracture energy index, elastic energy index, and free volume index described above have small values, the impact resistance is poor. Samples having large values of Formulas 2-1 to 2-3 and 3-1 to 3-3 substantially have excellent pen drop test results. For example, if the fracture energy index, elastic energy index, and free volume index have large values, the impact resistance is excellent.
[0235] Preparation Example 2: Evaluation of physical properties according to the quenching process when manufacturing glass products
[0236] In Preparation Example 1, glass product samples for physical property evaluation only were prepared, molded into block samples, and tested. A glass product 100 that can be incorporated into an actual display device (such as a cover window for a foldable display device) can be manufactured by a process different from the manufacturing process of Preparation Example 1. The glass product 100 can be manufactured by performing a quenching process of the glass composition using a roller instead of a carbon mold during the manufacturing process of Preparation Example 1. The glass product 100 of this Preparation Example is different from the glass product 100 in Preparation Example 1 in that it is manufactured by performing a quenching process using a glass sheet instead of a glass block, and the chemical strengthening process performed in Preparation Example 1 is not performed.
[0237] The elastic energy index and free volume index (which are defined in Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3) of the glass article 100 manufactured by the manufacturing process described above were calculated and shown in Table 3 below.
[0238] Table 3
[0239]
[0240]
[0241] Referring to Table 3, the glass product 100 subjected only to the quenching process in the manufacturing process of the glass product 100 is different from the glass product sample of Table 2 in terms of the values of Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3. However, in the glass product 100 of this preparation example, the elastic energy index and the free volume index of Sample #1 and Sample #2 are larger than those of the other samples, and Sample #1 and Sample #2 have excellent pen drop test results. For example, the glass product 100 manufactured in this preparation example is more consistent with the values of Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3 of Table 2 and the pen drop test results. For example, even when the glass product 100 is manufactured by performing the quenching process, the pen drop characteristics are excellent based on the values of Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3. Therefore, in the case of evaluating the physical properties or pen drop characteristics of the glass article 100, the impact resistance characteristics of the glass article 100 can be determined based on the physical properties of the glass article 100 itself and the values of Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3, without preparing a glass composition identical to the glass article 100, manufacturing a separate block sample, and evaluating its physical properties.
[0242] Table 4 below shows changes in physical properties of the glass article sample of Preparation Example 1 and the glass article 100 of Preparation Example 2.
[0243] Table 4
[0244] Physical properties Change CTE 2.0(-) <![CDATA[T g ]]> 0.3(-) ρ 0.3(-) E 4.0(-) v 1.0(+) <![CDATA[H v ]]> 5.7(-) <![CDATA[K IC ]]> 8.0(+) B 15.6(-)
[0245] In Table 4, the "change amount" indicates the degree of change compared to the reference sample, rather than the absolute numerical change amount. Referring to Table 4, when the quenching process is performed during the manufacturing process of the glass article 100, various physical properties of the glass article 100 (such as the coefficient of thermal expansion CTE, the glass transition temperature T g , density ρ, Young's modulus E, Poisson's ratio v, hardness H v , fracture toughness K IC and brittleness B) changes. Although the physical properties do not necessarily change with a specific trend, the glass article 100 subjected to the quenching process has such physical properties that the values according to Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3 are consistent with the pen drop test results. The glass article 100 according to one embodiment may have excellent pen drop characteristics because the values according to Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3 satisfy a specific range, and may have impact resistance characteristics suitable for application to foldable display products.
[0246] Preparation Example 3: Evaluation of physical properties according to quenching process and chemical strengthening process
[0247] Unlike Preparation Example 2, a glass article 100 was prepared and subjected to a quenching process and the same chemical strengthening process as in Preparation Example 1, and the elastic energy index and free volume index defined in Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3 were calculated and shown in Table 5 below.
[0248] Table 5
[0249]
[0250] Referring to Table 5, the glass product 100 subjected to the quenching process and the chemical strengthening process in the manufacturing process of the glass product 100 is different from the glass product samples of Tables 2 and 3 in terms of the values in Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3. However, in the glass product 100 of this preparation example, the elastic energy index and the free volume index of Sample #1 and Sample #2 are larger than those of the other samples, and Sample #1 and Sample #2 have excellent pen drop test results. For example, the glass product 100 manufactured in this preparation example is more consistent with the values of Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3 of Table 2 and the pen drop test results. For example, in the case of the glass product 100 manufactured by performing the quenching process, based on the values of Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3, the pen drop characteristics are excellent.
[0251] Table 6 below shows changes in physical properties of the glass article sample of Preparation Example 1 and the glass article 100 of Preparation Example 3.
[0252] Table 6
[0253] Physical properties Change CTE 1.6(-) <![CDATA[T g ]]> 0.3(-) ρ 0.3(-) E 3.0(-) v - <![CDATA[H v ]]> 3.0(-) <![CDATA[K IC ]]> 8.0(+) B 15.6(-)
[0254] In Table 6, the "change amount" indicates the degree of change compared to the reference sample, rather than the absolute numerical change amount. Referring to Table 6, when the quenching process and the chemical strengthening process are performed during the manufacturing process of the glass article 100, various physical properties of the glass article 100 (such as the coefficient of thermal expansion CTE, the glass transition temperature T g , density ρ, Young's modulus E, Poisson's ratio v, hardness H v , fracture toughness K IC and brittleness B) changes. Although the physical properties do not necessarily change with a specific trend, the glass product 100 subjected to the quenching process and the chemical strengthening process has physical properties whose values according to Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3 are consistent with the pen drop test results. The glass product 100 according to the embodiment has excellent pen drop characteristics because the values according to Formulas 2-1 to 2-3 and Formulas 3-1 to 3-3 satisfy a specific range, and has impact resistance characteristics suitable for use in foldable display products.
[0255] At the end of the detailed description, those skilled in the art will appreciate that many changes and modifications may be made to the embodiments without departing substantially from the principles of the present disclosure. Therefore, the embodiments of the present disclosure disclosed are used only in an overview and descriptive sense, and not for a limiting purpose.
Claims
1. Glass products, in, The glass article has a thickness in the range of 20 μm to 150 μm, The first elastic energy index defined by the following formula 2-1 is equal to or greater than 0.8*10 5 MPa / m 1.5 : The first elastic energy index E elas1 =(1 / B)*E abs (Formula 2-1), Among them, "B" is brittleness, and "E abs ” is the absorbed energy defined by the following formula A: Absorption energy E abs =σ 2 *(1-v) / E (Formula A) Where "σ" is the surface intensity and is defined by the following Equation B: Surface strength σ=(E*α*ρ 2 ) / (1-v) (Formula B) where "E" is Young's modulus, "α" is the coefficient of thermal expansion, "ρ" is the density, and "v" is the Poisson's ratio, and The stretch index β is defined by the following formula 2: KWW Equal to or greater than 0.95: Where "D" is the intensity factor, where D = B VFT / T0, "T0" is the Vogel temperature, "T g ” is the glass transition temperature, and "B VFT ” is the viscosity at T0.
2. The glass product according to claim 1, wherein: The first elastic energy index is equal to or greater than 0.9*10 5 MPa / m 1.5 .
3. The glass product according to claim 1, in, The second elastic energy index defined by the following formula 2-2 is equal to or greater than 0.1*10 -4 (kJ / m 2 ) 2 : The second elastic energy index E elas2 =G IC *(1 / B) 6 *E abs (Formula 2-2), Among them, "B" is brittleness, "E abs " is the absorbed energy, and "G IC ” is the fracture energy index according to the following formula 1: Fracture energy index G IC =(K IC 2 *(1-v 2 )) / E (Formula 1), Among them, "K IC ” is the fracture toughness, “v” is the Poisson’s ratio, and “E” is the Young’s modulus.
4. The glass product according to claim 3, wherein: The second elastic energy index is equal to or greater than 0.12*10 -4 (kJ / m 2 ) 2 .
5. The glass product according to claim 3, wherein: The fracture energy index is equal to or greater than 150 kJ / m 2 .
6. The glass product according to claim 3, in, The third elastic energy index defined by the following formula 2-3 is equal to or greater than 2.1 MPa 2 / m 0.5 : The third elasticity index E elas3 =G IC *(1 / B)*E abs (Formula 2-3) Among them, "G IC " is the fracture energy index, "B" is brittleness, and "E abs ” is absorbed energy.
7. The glass product according to claim 6, wherein: The third elastic energy index is equal to or greater than 2.3 MPa 2 / m 0.5 .
8. The glass product according to claim 1, wherein: The crack generation height in the pen drop test performed with a pen whose ball diameter was 0.7 mm and whose weight was 1.12 g was equal to or greater than 6 cm.
9. The glass product according to claim 1, wherein: The glass article comprises SiO2, Al2O3 and at least one metal oxide, The variable defined as the ratio of the content of the monovalent metal oxide to the content of the divalent metal oxide in the at least one metal oxide is in the range of 7.0 to 8.5, and The ratio of the content of Al2O3 to the total content of the at least one metal oxide is in the range of 0.3 to 0.
4.
10. Glass products, in, The glass article has a thickness in the range of 20 μm to 150 μm, The first free volume index defined by the following formula 3-1 is equal to or greater than 0.001K -1 : The first free volume index V t1 =1 / T g (Formula 3-1), Among them, "T g ” is the glass transition temperature, and The stretch index β is defined by the following formula 2: KWW Equal to or greater than 0.95: Where "D" is the intensity factor, where D = B VFT / T0, "T0" is the Vogel temperature, "T g ” is the glass transition temperature, and "B VFT ” is the viscosity at T0.
11. The glass product according to claim 10, in, The second free volume index defined by the following formula 3-2 is equal to or greater than 7.0*10 -8 (kJ / m 2 ) 2 / K: Second free volume index V t2 =G IC *(1 / B) 6 *E abs *(1 / T g ) (Formula 3-2), Among them, "T g ” is the glass transition temperature, "B" is the brittleness, and "G IC ” is the fracture energy index defined by the following formula 1: Fracture energy index G IC =(K IC 2 *(1-v 2 )) / E (Formula 1), Among them, "K IC ” is the fracture toughness, "v" is the Poisson's ratio, and "E" is the Young's modulus, "E abs ” is the absorbed energy and is defined by the following formula A: Absorption energy E abs =σ 2 *(1-v) / E (Formula A) Where "σ" is the surface intensity and is defined by the following Equation B: Surface strength σ=(E*α*ρ 2 ) / (1-v) (Formula B), Wherein, "E" is Young's modulus, "α" is the coefficient of thermal expansion, "ρ" is the density, and "v" is the Poisson's ratio.
12. The glass product according to claim 11, wherein: The second free volume index is equal to or greater than 10.0*10 -8 (kJ / m 2 ) 2 / K.
13. The glass product according to claim 12, in, The third free volume index defined by the following formula 3-3 is equal to or greater than 6.0*10 -14 MPa 4 / (m 2.5 *K 3 ): The third free volume index V t3 =G IC *(1 / B)*E abs *σ*(1 / (T g ) 3 ) (Formula 3-3), Among them, "T g " is the glass transition temperature, "G IC " is the fracture energy index, "B" is brittleness, "E abs ” is the absorption energy, and “σ” is the surface strength.
14. The glass product according to claim 13, wherein: The third free volume index is equal to or greater than 9.0*10 -14 MPa 4 / (m 2.5 *K 3 ).
15. The glass article according to claim 10, wherein: The crack generation height in the pen drop test performed with a pen whose ball diameter was 0.7 mm and whose weight was 1.12 g was equal to or greater than 6 cm.
16. The glass article according to claim 10, wherein: The glass article comprises SiO2, Al2O3 and at least one metal oxide, The variable defined as the ratio of the content of the monovalent metal oxide to the content of the divalent metal oxide in the at least one metal oxide is in the range of 7.0 to 8.5, and The ratio of the content of Al2O3 to the total content of the at least one metal oxide is in the range of 0.3 to 0.
4.
17. A display device comprising: A display panel including a plurality of pixels; A cover window, arranged above the display panel; as well as an optically transparent bonding layer, disposed between the display panel and the cover window, Wherein, the cover window comprises a glass product having a thickness ranging from 20 μm to 100 μm, The first elastic energy index of the glass product is equal to or greater than 0.8*10 5 MPa / m 1.5 , and is defined by the following formula 2-1: The first elastic energy index E elas1 =(1 / B)*E abs (Formula 2-1), Among them, "B" is brittleness, and "E abs ” is the absorbed energy and is defined by the following formula A: Absorption energy E abs =σ 2 *(1-v) / E (Formula A), Where "σ" is the surface intensity and is defined by the following Equation B: Surface strength σ=(E*α*ρ 2 ) / (1-v) (Formula B), where "E" is Young's modulus, "α" is the coefficient of thermal expansion, "ρ" is the density, and "v" is the Poisson's ratio, and The first free volume index of the glass article is equal to or greater than 0.001K -1 , and is defined by the following formula 3-1: The first free volume index V t1 =1 / T g (Formula 3-1), Among them, "T g ” is the glass transition temperature, and The tensile index β of the glass article KWW is equal to or greater than 0.95, and is defined by the following Formula 2: Where "D" is the intensity factor, where D = B VFT / T0, "T0" is the Vogel temperature, "T g ” is the glass transition temperature, and "B VFT ” is the viscosity at T0.
18. The display device according to claim 17, wherein: In the glass product, The second elastic energy index defined by the following formula 2-2 is equal to or greater than 0.1*10 -4 (kJ / m 2 ) 2 : The second elastic energy index E elas2 =G IC *(1 / B) 6 *E abs (Formula 2-2), Among them, "B" is brittleness, "E abs " is the absorbed energy, and "G IC ” is the fracture energy index according to the following formula 1: Fracture energy index G IC =(K IC 2 *(1-v 2 )) / E (Formula 1), Among them, "K IC ” is the fracture toughness, "v" is the Poisson's ratio, and "E" is the Young's modulus, and The third elastic energy index defined by the following formula 2-3 is equal to or greater than 2.1 MPa 2 / m 0.5 : The third elasticity index E elas3 =G IC *(1 / B)*E abs (Formula 2-3), Among them, "G IC " is the fracture energy index, "B" is brittleness, and "E abs ” is absorbed energy.
19. The display device according to claim 17, wherein: In the glass product, The second free volume index defined by the following formula 3-2 is equal to or greater than 7.0*10 -8 (kJ / m 2 ) 2 / K: Second free volume index V t2 =G IC *(1 / B) 6 *E abs *(1 / T g ) (Formula 3-2), Among them, "T g ” is the glass transition temperature, "B" is the brittleness, and "G IC ” is the fracture energy index defined by the following formula 1: Fracture energy index G IC =(K IC 2 *(1-v 2 )) / E (Formula 1), Among them, "K IC ” is the fracture toughness, "v" is the Poisson's ratio, "E" is the Young's modulus, and "E abs ” is the absorbed energy, and The third free volume index defined by the following formula 3-3 is equal to or greater than 6.0*10 -14 MPa 4 / (m 2.5 *K 3 ): The third free volume index V t3 =G IC *(1 / B)*E abs *σ*(1 / (T g ) 3 ) (Formula 3-3), Among them, "T g " is the glass transition temperature, "G IC " is the fracture energy index, "B" is brittleness, "E abs ” is the absorption energy, and “σ” is the surface strength.
20. The display device according to claim 17, wherein: The glass article comprises SiO2, Al2O3 and at least one metal oxide, The variable defined as the ratio of the content of the monovalent metal oxide to the content of the divalent metal oxide in the at least one metal oxide is in the range of 7.0 to 8.5, and The ratio of the content of Al2O3 to the total content of the at least one metal oxide is in the range of 0.3 to 0.4.
Citation Information
Patent Citations
Digital twin-based smart farm method, management device and computer program
KR1020230100092A